Enterovirus vesicular stomatitis with exanthema: Epidemiological Features and Vaccination - Yu. S. Sytaya; A. Ya. Mindlina (Эпидемиология и вакцинопрофилактика)
Relevance. Hand, foot and mouth disease (HFMD) is a disease that is extremely relevant for the Russian Federation. According to modern data, epidemic outbreaks of severe course involving a large number of children are registered in the Russian Federation. At the same time, the mortality rate varies worldwide and can range from 6.46 to 51.00 per 100 thousand population. In addition, the fact that the Russian Federation borders with East and Southeast Asia annually increases the risk of HFMD entering the territory of Russia. Every year, the disease causes more than 2 million hospitalizations in Asia. Aims. According to the literature, to analyze the epidemiological characteristics of HFMD in the Russian Federation and the world, as well as the prospects for vaccination of this infection. To achieve this goal, open sources hosted in the electronic databases PubMed, Medline and e-Library were used. Publications on enterovirus infection for the period from 2014 to 2022 are analyzed. The WHO (Western Pacific Region) statistics on HFMD were also used. Results. According to the modern literature, HFMD is the most common clinical form of enterovirus infection, which is characterized by high heterogeneity of pathogens. Over the past few years, the incidence of enterovirus infection in many subjects of the Russian Federation has been characterized by an upward trend. The most unfavorable epidemic situation in the Russian Federation is observed on the territory of the Far Eastern Federal District, where the largest number of cases of enterovirus infection is registered. In 2018, 1058 cases of enterovirus infection were detected in the Sakhalin region (222.6 cases per 100 thousand). The structure of enterovirus infection in the Russian Federation is dominated by exanthemic forms, herpangina and gastroenteritis. It is necessary to consider the introduction of vaccination of the child population, since rises in the incidence of enterovirus infection in various regions are registered annually on the territory of the Russian Federation. Vaccines against EV-A71 are already being used in China for epidemic indications. The active circulation of HFMD in the Asia-Pacific region may affect the spread of enterovirus infection in the territory of the Russian Federation, as the risk of imported cases of infection and the formation of epidemic foci of group morbidity increases.